Estimating the nonlinear effects of female directors on financial performance - Chen, Ming; Lim, Hock Eam (Emerald Group Publishing Limited, 2016)
Purpose – The purpose of this paper is to identify the non-linear effects of the presence of women directors on the board on the financial performances of Malaysian companies which undertakes initial public offerings (IPOs).This paper also analyzes the impacts of non-executive directors and independent directors on their company performances. Design/methodology/approach – This paper traces the effects of gender diversity on the board on the financial performance of a sample of 123 Malaysian companies from the list of 230 companies which have made IPOs and are listed during the period 2005-2012.The multiple regressions (with linear and non-linear specification) are used to estimate the effects of women directors on companies’ performance. Findings – The results show that presence of women directors on the board do not purport to have any significant linear or non-linear impact on the financial performance of the companies under reference, except for the companies in the top 80th percentile of return on equity. Similarly, strong evidence is also found when the number of women as board members is more than 15 per cent. Research limitations/implications – The findings of this paper suggest that presence of women directors provides a beneficial impact on the return on equity of companies in Malaysia. Therefore, it is suggested that there should be greater participation of women as board members in the country.Originality/value – Prior studies tried to estimate linear relationship between the presence of woman directors on company performance.Present study assessed it from three different angles: the sample consists of companies in Malaysia issuing IPOs; possible non-linear relationship is also assessed; and apart from multiple regression, quantile regression technique was also used.